Determining a method to measure the capital intensity for enterprises listed in the industrial sector of the Johannesburg Stock Exchange for the period 1989 to 1996 - Erasmus, Petrus Daniel (Stellenbosch : Stellenbosch University, 2012)
Assignment (MComm)--University of Stellenbosch, 2001.